UNDANGAN PAPERLESS BERBASIS CLOUD COMPUTING DENGAN MEMANFAATKAN CLOUDINARY - Astika Ayuningtyas; Alif Restu Pramudi (Institut Teknologi Dirgantara Adisutjipto, 2017)
Paperless is an attempt to reduce the use of paper media in the filing process, a use of paperless office technology, paperless office technology will be applied using cloud computing technology. Cloud computing is a service that provides synchronized online storage media, which can be accessed through a variety of devices such as Android smartphones. Cloud services applications built on these systems is a data storage service to take advantage of the cloudinary storage media. Cloudinary is a service that provides cloud services for image, download and CDN (Content Delivery Network). This can certainly provide convenience in the process of registering and sending out invitations electronically using paperless invitations. In addition, there is a process of checking the read (read) status will be performed by the MySQL database system to use the webservice. Paperless invitations applications can be run if the user has an e-mail account, the paperless invitations test system that have been made show the menu each function can be executed according to its input.